2022
DOI: 10.2147/jhc.s373112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early TACE Refractoriness on Survival in Patients with Hepatocellular Carcinoma: A Real-World Study

Abstract: Purpose To investigate the effect of early transarterial chemoembolization (TACE) refractoriness on hepatocellular carcinoma (HCC) patient survival and to explore whether viable lesions > 50% after two consecutive TACE treatments negatively affect the prognosis of HCC patients. Patients and Methods From January 2014 to August 2017, 323 HCC patients who received TACE as the initial treatment were analyzed. TACE refractoriness was diagnosed according to the Japan Society … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…By controlling the intrahepatic tumor burden, there is a potential to improve liver function, PFS, and allow for a longer duration of systemic therapy, ultimately enhancing the effectiveness of overall treatment. 8 , 26 As research on anti-VEGF drug and immune checkpoint inhibitors deepens, the rationality of TACE-based combination therapy is gradually being accepted. Firstly, after TACE treatment, tumor cells induce upregulation of HIF-1α in the hypoxic environment, leading to upregulation of VEGF and platelet-derived growth factor (PDGF) expression.…”
Section: Discussionmentioning
confidence: 99%
“…By controlling the intrahepatic tumor burden, there is a potential to improve liver function, PFS, and allow for a longer duration of systemic therapy, ultimately enhancing the effectiveness of overall treatment. 8 , 26 As research on anti-VEGF drug and immune checkpoint inhibitors deepens, the rationality of TACE-based combination therapy is gradually being accepted. Firstly, after TACE treatment, tumor cells induce upregulation of HIF-1α in the hypoxic environment, leading to upregulation of VEGF and platelet-derived growth factor (PDGF) expression.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Yang et al, the median overall survival in TACE responsive HCC was 34 months following TACE, whereas it was 21 months in non-responsive tumors. 10 Another study showed the median survival time to be 37 months following first session of TACE. 11 Trans-arterial radioembolisation (TARE) is a further advancement in TACE which is gaining popularity.…”
Section: Original Articlementioning
confidence: 99%
“… 11 However, there is still no consensus on this concept in the international community, and TACE refractoriness does not fully represent the poor prognosis. 12 More importantly, the above criteria cannot reliably reflect the long-term prognosis of patients directly and cannot accurately stratify patients before treatment. Although studies have used clinical information or extracted imaging features to develop a model to predict the efficacy of TACE.…”
Section: Introductionmentioning
confidence: 99%